Enhancing transparency, accountability and effectiveness of supreme audit institutions of India through communication network - Bhatnagar, P.S.; Sharma, Supriya (2016)
Supreme Audit Institutions (SAIs) are public sector organisations independent of government and accountable to the national and state legislatures responsible for overseeing the auditing of the government financial operations. SAIs are playing vital role in good governance and to enhance their own role and making their functioning more effective, they are using various new tools and techniques. Communication capacity with various stakeholders is one such tool that can enhance their functioning. SAIs are using various techniques of communication which are generally divided into internal and external communication. This article is about how SAIs in India are proactively setting an example for an open, accountable and transparent institutions under the frame of their comprehensive external communication strategies.
Keywords: Accountability; Audit